2022
DOI: 10.3390/jcm11030871
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Negative Automatic Thoughts and Psychological Inflexibility in Schizophrenia

Abstract: Background: Schizophrenia is one of the most severe disorders in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) spectrum. Negative automatic thoughts (NAT), cognitive fusion (CF), and experiential avoidance (EA), as part of psychological inflexibility (PI), can be considered important dysfunctional cognitive processes in schizophrenia. Methods: In the present study, two samples were included: a target group consisting of 41 people with schizophrenia (23 females; aged 44.98 ± 11.74), and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This approach targets psychological inflexibility as a common process involved in the onset of psychological disorders associated with chronic pain, including cognitive fusion, experiential and behavioral avoidance [41][42][43]. Psychological inflexibility is defined as the excessive influence of thoughts and emotions over behavioral choices, resulting in the difficulty to adapt to different life contexts, including chronic pain [42,44].…”
Section: Introductionmentioning
confidence: 99%
“…This approach targets psychological inflexibility as a common process involved in the onset of psychological disorders associated with chronic pain, including cognitive fusion, experiential and behavioral avoidance [41][42][43]. Psychological inflexibility is defined as the excessive influence of thoughts and emotions over behavioral choices, resulting in the difficulty to adapt to different life contexts, including chronic pain [42,44].…”
Section: Introductionmentioning
confidence: 99%
“… 15 These psychosocial risk factors play a pivotal role to initiate and facilitate unhealthy habits, such as poor treatment compliance, unhealthy dietary pattern, lack of physical activity, 16 excessive drinking, smoking, and sleeping problems, 17 which contribute to the generation and development of cardiovascular diseases, diabetes mellitus, and MetS. 18 Prior investigations have indicated that negative affect and internalized stigma are not only less valuable because they have a mental illness, 19 but can also be obstacles to treatment adherence and negatively influence long-term recovery. 20 However, studies on the psychosocial risk mechanisms of MetS in SCZ are limited; thus, further research would provide useful insights into this issue.…”
Section: Introductionmentioning
confidence: 99%
“…This approach targets psychological inflexibility as a common process involved in the onset of psychological disorders associated with chronic pain, including cognitive fusion, emotional suppression, experiential and behavioural avoidance [31][32][33]. These processes result in the patient's incapacity to adapt to various life circumstances, including the aversive experience of pain [32,34].…”
Section: Introductionmentioning
confidence: 99%
“…The healthier variant is represented by acceptance, or the willingness to fully experience emotions or sensations, whether pleasant or not, without attempts to control them, facilitating adaptation in the case of chronic pain [38,39]. From a behavioural point of view, difficulties are linked to the use of unhealthy coping strategies, inconsistent with the patient's aspirations, especially in the context of a chronic health condition [30,33]. On the other hand, increasing values-based action was associated with less disability and elevated motivation in chronic pain [40].…”
Section: Introductionmentioning
confidence: 99%